Unsaturated coordination polymer frameworks as multifunctional sulfur reservoir for fast and durable lithium-sulfur batteries. (January 2021) - Zhu, Yanfei; Li, Gaoran; Luo, Dan; Wan, Hui; Feng, Ming; Yuan, Dingwang; Hu, Wangyu; Li, Zhaoqiang; Gao, Rui; Zhang, Zhen; Liu, Wenwen; Li, Matthew; et al.
Abstract: Desirable sulfur electrochemistry strongly relies on host-guest interactions, which calls for rational designs on the surface fine structure of sulfur reservoir materials. Herein, we for the first time, explore the coordinative unsaturation in ferric hexacyanoferrate (FeHCF) for sulfur immobilization and catalyzation towards improved lithium-sulfur (Li–S) batteries. A simple ammonia etching treatment is implemented to selectively remove Fe III –H2 O moieties, leaving vast coordinatively unsaturated Fe sites with a simultaneous establishment of considerable mesoporosity in the activated matrix (denoted as FeHCF-A). As a sulfur-host, the massive meso-scale channels endow FeHCF-A with abundant active interfaces and ion/mass transfer pathways, while more importantly, the coordinatively unsaturated Fe sites are revealed with higher adsorbability and conversion catalytic activity to polysulfides. Attributed to theses chemical and structural superiorities, the as-developed FeHCF-A enables a fast, stable, and efficient sulfur electrochemistry, e.g., good rate capability up to 5C and excellent cyclability with an ultralow decay rate of 0.024% per cycle over 500 cycles, as well as a commendable areal capacity of 4.5 mAh cm −2 under high sulfur loading. This work affords a new and insightful perspective of coordinative chemistry for material engineering in Li–S batteries as well as other related fields. Graphical abstract: The synergistically combination of unique porosity and unsaturated active Fe sites of FeHCF-A contributes to enhanced adsorption and rapid catalytic conversion of lithium polysulfides. Image 1 Highlights: Ammonia etching method is firstly implemented to construct coordinatively unsaturated Fe sites. The coordinatively unsaturated Fe sites contribute to enhanced adsorption and catalytic conversion of lithium polysulfides. The mesoporosity in FeHCF-A enables the composite electrode with high sulfur loading and areal capacity.